2015 ASEE Annual Conference and Exposition Proceedings
DOI: 10.18260/p.23881
|View full text |Cite
|
Sign up to set email alerts
|

Difference Between Engineering Men and Women: How and Why They Choose What They Do During Early Career

Abstract: Retention of the engineering workforce is of national importance for global competitiveness. Retention of women engineers is of particular interest because of the impact of their lower starting representation and higher attrition rate on workforce diversity. Exit rates from engineering careers are highest in the first 10 years after graduation. Thus, unlike most workforce retention research, this study focuses on participants who are still in the midst of this critical phase of their careers. We investigated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…For example, understanding why women leave the engineering workforce (VanAntwerp & Wilson, 2015), how to improve the experiences of transfer students from community colleges into 4-year institutions (Pieri et al, 2015), and strategies for dual-career couples searching for employment in academia (Ciston et al, 2015).…”
Section: Publication Research Questions and Purposementioning
confidence: 99%
“…For example, understanding why women leave the engineering workforce (VanAntwerp & Wilson, 2015), how to improve the experiences of transfer students from community colleges into 4-year institutions (Pieri et al, 2015), and strategies for dual-career couples searching for employment in academia (Ciston et al, 2015).…”
Section: Publication Research Questions and Purposementioning
confidence: 99%
“…One such study explored motivations for early career choices among a small, representative group of 11 male and 11 female undergraduates. 12 Ultimately, the women and men studied were similarly motivated in their career choices, partitioned almost equally across the entire spectrum of Self Determination Theory. But, they discussed these motivations remarkably differently, with men especially interested in the technology while the women were much more focused on business-and people-related (i.e.…”
mentioning
confidence: 99%
“…However, there is not much evidence that lack of interest would fully explain the higher exit rate of women compared to men. A qualitative study reported that both men and women displayed a strong intrinsic interest in engineering work [77], but pointed out that intrinsic interests can be diminished over time as a result of the physical and social environment. Thus, a chilly or hostile climate could be intertwined in complex ways with career exits blamed simply on "change of interest."…”
Section: Women In the Engineering Workplace (Outside Of Academia)mentioning
confidence: 99%